A laudable strategy to manage bacterial panicle blight disease of rice using biocontrol agents - Ngalimat, Mohamad S.; Mohd Hata, Erneeza; Zulperi, Dzarifah; Ismail, Siti I.; Ismail, Mohd R.; Mohd Zainudin, Nur A. I.; Saidi, Noor B.; Yusof, Mohd T. (Wiley, 2023)
Bacterial panicle blight (BPB) disease is a dreadful disease in rice-producing countries. Burkholderia glumae, a Gram-negative, rod-shaped, and flagellated bacterium was identified as the primary culprit for BPB disease. In 2019, the disease was reported in 18 countries, and to date, it has been spotted in 26 countries. Rice yield has been reduced by up to 75 worldwide due to this disease. Interestingly, the biocontrol strategy offers a promising alternative to manage BPB disease. This review summarizes the management status of BPB disease using biological control agents (BCA). Bacteria from the genera Bacillus, Burkholderia, Enterobacter, Pantoea, Pseudomonas, and Streptomyces have been examined as BCA under in vitro, glasshouse, and field conditions. Besides bacteria, bacteriophages have also been reported to reduce BPB pathogens under in vitro and glasshouse conditions. Here, the overview of the mechanisms of bacteria and bacteriophages in controlling BPB pathogens is addressed. The applications of BCA using various delivery methods could effectively manage BPB disease to benefit the agroecosystems and food security.